DIGITALIZATION OF MADRASAHS AND ITS RELATIONSHIP WITH EDUCATOR AND STAFF PERFORMANCE - Encu, Asep; Nurfalah, Diki (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
As Islamic educational institutions, madrasahs hold a strategic role in shaping morally grounded and knowledgeable generations amid the era of digital transformation. The digitalization of madrasahs constitutes a critical aspect of educational modernization, impacting various dimensions of institutional performance, particularly among educators and administrative staff. This study investigates the correlation between the implementation of digitalization in madrasahs and the performance of educators and education personnel at State Islamic Senior High Schools (Madrasah Aliyah Negeri) across Bandung Regency. Employing a descriptive quantitative design with a correlational approach, data were gathered through structured surveys and analyzed using Pearson’s correlation test. The findings reveal a statistically significant positive relationship between madrasah digitalization and staff performance (p = 0.005, p < 0.05), indicating that the integration of digital systems contributes meaningfully to improving the operational effectiveness of Islamic educational institutions, especially at the senior secondary level.